2016
DOI: 10.4102/sajim.v18i1.694
|View full text |Cite
|
Sign up to set email alerts
|

Use of Web 2.0 by students in the Faculty of Information Science and Communications at Mzuzu University, Malawi

Abstract: Background: Over the years, advancements in Internet technologies have led to the emergence of new technologies such as Web 2.0, which have taken various sectors including higher education by storm. Web 2.0 technologies are slowly but surely penetrating higher education in developing countries with much hype, according to the literature. This justifies the need for original research that aims at demystifying the application and exploiting the promises that come along with these so-called versatile technologies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
32
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 35 publications
3
32
0
1
Order By: Relevance
“…Other students found Twitter useful because it helped them connect with their current and old friends online. These findings corroborate with earlier findings by Chawinga and Zinn (2016) in which they found that students in Malawi usually use social media such as Facebook, Twitter and WhatsApp to instantly connect with peers currently at the university or at home and to search and locate old friends. The fact that best grades came from group blog posts (as evidenced by an analysis of the tweets and blog posts), suggest that working in groups motivates students to work hard and understand the content better.…”
Section: Factors For Use or Non-use Of Social Mediasupporting
confidence: 83%
See 3 more Smart Citations
“…Other students found Twitter useful because it helped them connect with their current and old friends online. These findings corroborate with earlier findings by Chawinga and Zinn (2016) in which they found that students in Malawi usually use social media such as Facebook, Twitter and WhatsApp to instantly connect with peers currently at the university or at home and to search and locate old friends. The fact that best grades came from group blog posts (as evidenced by an analysis of the tweets and blog posts), suggest that working in groups motivates students to work hard and understand the content better.…”
Section: Factors For Use or Non-use Of Social Mediasupporting
confidence: 83%
“…For example, in Africa, more specifically at the University of the Western Cape in South Africa, Dzvapatsva, et al (2014) report that some of the factors that militate against the use of social media include lack of technical skills that students experience when learning or using portals of social media, inadequate technological infrastructure and bandwidth which results in students abusing it. The problem of Internet bandwidth seems to be common in most African countries because Chawinga and Zinn (2015) also reports of a similar problem at MZUNI in Malawi. Additionally, literature shows that opponents of social media use in a classroom continue to downplay the value of such technologies.…”
Section: Challenges That Affect Incorporation Of Social Media In Pedamentioning
confidence: 99%
See 2 more Smart Citations
“…Again, both the system's network failings and Internet outages can further be attributed to electricity blackouts, which are prevalent in Malawi, thereby affecting operations of ICT equipment such as computers and servers. Electricity outages are chronic in Malawi as reported by various scholars (Chawinga, 2017;Chawinga & Zinn, 2015;Chawinga & Zinn, 2016). To improve the system quality, it is necessary for the court authorities and stakeholders to ensure that the Internet is improved through identifying reliable Internet service providers and making sure that alternative sources of power supply such as solar and generators are procured to supply power when electricity from the national grid is cut off.…”
Section: System Qualitymentioning
confidence: 99%